Anti-cracking performance evaluation method for asphalt stress absorbing layer and computer equipment

By conducting oblique shear tests on the asphalt stress absorbing layer specimens, the bonding coefficient and stress absorption coefficient between layers are calculated, and the problem of insufficient crack resistance evaluation index in the existing technology is solved, and an efficient and accurate evaluation method is achieved.

CN119555587AActive Publication Date: 2025-03-04佛交科天诺(广东)材料有限公司 +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411601826.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-04
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

When evaluating the crack resistance of the asphalt stress absorbing layer, the index is insufficient and not systematic, resulting in insignificant results in actual engineering.

Method used

By conducting oblique shear tests on the stress absorbing layer specimen, relevant index information is collected, and the interlayer bonding coefficient and interlayer stress absorption coefficient are calculated to evaluate crack resistance.

Benefits of technology

The intuitive, accurate and efficient evaluation of the crack resistance of the asphalt stress absorber layer is achieved, avoiding the complexity and inefficiency of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555587A_ABST
    Figure CN119555587A_ABST
Patent Text Reader

Abstract

The invention discloses a crack resistance evaluation method for an asphalt stress absorbing layer and computer equipment, and relates to the technical field of pavement engineering.The method comprises the steps that an oblique shear test is conducted on a stress absorbing layer test piece, and index information in the oblique shear test process is collected, the index information comprises a shearing angle, a stress load, vertical displacement, transverse displacement, interlayer dislocation displacement and stress absorption layer bonding force; calculating an interlayer bonding coefficient and an interlayer stress absorption coefficient of the stress absorption layer test piece according to the index information; and evaluating the crack resistance of the stress absorption layer test piece according to the interlayer bonding coefficient and the interlayer stress absorption coefficient. By adopting the method, the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer test piece can be introduced, and the crack resistance of the asphalt stress absorption layer can be accurately evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of pavement engineering, and in particular to a method and computer equipment for evaluating the anti-cracking performance of an asphalt stress absorbing layer. Background Art

[0002] Reflective cracks are one of the most common problems between asphalt surface and semi-rigid base, as well as between old road and asphalt overlay. Setting up a stress absorption layer can effectively delay the occurrence of reflective cracks, but its interlayer bonding performance and crack resistance still need to be further improved. Therefore, it is crucial to find a method to effectively evaluate the crack resistance of the stress absorption layer in order to prevent and control reflective cracks in the road surface.

[0003] The existing method for evaluating the anti-cracking performance of the stress absorption layer is generally to directly evaluate it through mechanical indicators obtained through direct shear tests, low-temperature semicircular bending tests and interlayer pull-out tests. However, the existing anti-cracking performance evaluation indicators are insufficient and unsystematic, and their effects are not significant when applied to actual projects.

[0004] Therefore, there is an urgent need to invent an intuitive, accurate and effective evaluation method for the anti-cracking performance of asphalt stress absorption layer. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method and computer equipment for evaluating the anti-cracking performance of an asphalt stress absorption layer, which can introduce the interlayer bonding coefficient and the interlayer stress absorption coefficient to accurately evaluate the anti-cracking performance of the asphalt stress absorption layer.

[0006] In order to solve the above technical problems, the present invention provides a method for evaluating the anti-cracking performance of an asphalt stress absorption layer, comprising: performing an oblique shear test on a stress absorption layer specimen, and collecting index information during the oblique shear test, the index information including shear angle, force load, vertical displacement, lateral displacement, interlayer misalignment displacement and adhesion of the stress absorption layer; calculating the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen based on the index information; and evaluating the anti-cracking performance of the stress absorption layer specimen based on the interlayer bonding coefficient and interlayer stress absorption coefficient.

[0007] As an improvement of the above scheme, the step of calculating the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information includes: calculating the interlayer direction load according to the shear angle and the force load; calculating the decomposition displacement of the vertical displacement in the interlayer direction according to the vertical displacement and the shear angle; calculating the decomposition displacement of the lateral displacement in the interlayer direction according to the lateral displacement and the shear angle; calculating the stress absorption displacement according to the decomposition displacement of the vertical displacement in the interlayer direction, the decomposition displacement of the lateral displacement in the interlayer direction and the interlayer dislocation displacement; calculating the interlayer bonding coefficient of the stress absorption layer specimen according to the stress absorption layer bonding force, the stress absorption displacement, the interlayer direction load and the decomposition displacement of the vertical displacement in the interlayer direction; calculating the interlayer stress absorption coefficient of the stress absorption layer specimen according to the stress absorption displacement, the decomposition displacement of the vertical displacement in the interlayer direction and the decomposition displacement of the lateral displacement in the interlayer direction.

[0008] As an improvement of the above solution, the step of calculating the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information includes:

[0009] According to formula F ’ =F×sinα, calculate the interlayer direction load F ’ , where α is the shear angle and F is the load;

[0010] According to the formula s1 = L1 × sinα, the vertical displacement is calculated as the decomposed displacement s1 in the interlayer direction, where L1 is the vertical displacement;

[0011] According to the formula s2 = L2 × cosα, the lateral displacement is calculated to decompose the displacement s2 in the interlayer direction, where L2 is the lateral displacement;

[0012] According to the formula Δx=s1+s2-x, the stress absorption displacement Δx is calculated, where x is the interlayer displacement;

[0013] According to the formula Calculate the interlayer bonding coefficient K1 of the stress absorption layer specimen, where F t is the bonding force of the stress absorbing layer;

[0014] According to the formula The interlaminar stress absorption coefficient K2 of the stress absorption layer specimen is calculated.

[0015] As an improvement of the above solution, the interlayer bonding coefficient and the interlayer stress absorption coefficient are positively correlated with the anti-cracking performance.

[0016] As an improvement of the above scheme, the step of evaluating the anti-cracking performance of the stress absorption layer specimen according to the interlayer bonding coefficient and the interlayer stress absorption coefficient includes: when the interlayer stress absorption coefficient is greater than a first absorption threshold and the interlayer bonding coefficient is greater than or equal to a second bonding threshold, or the interlayer stress absorption coefficient is greater than or equal to the second absorption threshold and the interlayer bonding coefficient is greater than the first bonding threshold, the anti-cracking performance of the stress absorption layer specimen is "good", the first absorption threshold is greater than the second absorption threshold, and the first bonding threshold is greater than the second bonding threshold; when the interlayer stress absorption coefficient is less than the second absorption threshold and the interlayer bonding coefficient is less than or equal to the first bonding threshold, or the interlayer stress absorption coefficient is less than or equal to the first absorption threshold and the interlayer bonding coefficient is less than the second bonding threshold, the anti-cracking performance of the stress absorption layer specimen is "general"; otherwise, the anti-cracking performance of the stress absorption layer specimen is "good".

[0017] As an improvement of the above scheme, the molding steps of the stress absorption layer specimen include: constructing an asphalt mixture plate specimen; spreading a stress absorption layer on the asphalt mixture plate specimen; sequentially standing and heat-insulating the asphalt mixture plate specimen after spreading the stress absorption layer; evenly paving the asphalt mixture on the stress absorption layer of the asphalt mixture plate specimen after the insulation treatment, and rolling it into shape; sequentially standing and demolding the asphalt mixture plate specimen after rolling; coring the demolded asphalt mixture plate specimen to form a stress absorption layer specimen; and performing end surface grinding on the stress absorption layer specimen so that the stress absorption layer is in the middle position of the stress absorption layer specimen.

[0018] As an improvement of the above scheme, the step of spreading the stress absorption layer on the asphalt mixture plate specimen includes: when the stress absorption layer is a rubber asphalt stress absorption layer, spreading rubber asphalt on the asphalt mixture plate specimen; when the stress absorption layer is a single-layer rubber asphalt gravel stress absorption layer, spreading rubber asphalt on the asphalt mixture plate specimen, spreading gravel pre-wrapped with rubber asphalt on the rubber asphalt, and lightly pressing the gravel to embed the gravel into the asphalt; when the stress absorption layer is a double-layer rubber asphalt gravel stress absorption layer, spreading rubber asphalt on the asphalt mixture plate specimen, spreading gravel pre-wrapped with rubber asphalt on the rubber asphalt, lightly pressing the gravel to embed the gravel into the asphalt, and then spreading rubber asphalt, spreading gravel pre-wrapped with rubber asphalt on the rubber asphalt, and then lightly pressing the gravel to embed the gravel into the asphalt.

[0019] As an improvement of the above scheme, the steps of conducting an oblique shear test on the stress absorption layer specimen and collecting index information during the oblique shear test include: placing the stress absorption layer specimen in a temperature-controlled box for insulation treatment; using an oblique shear test fixture to conduct an oblique shear test on the stress absorption layer specimen; during the oblique shear test, uniformly loading the stress absorption layer specimen until the stress absorption layer specimen reaches a target degree of damage; collecting the shear angle, force load, vertical displacement, lateral displacement and adhesion of the stress absorption layer during the test; after the oblique shear test, removing the stress absorption layer specimen for static treatment; measuring the interlayer misalignment displacement between the upper test block and the lower test block of the stress absorption layer specimen.

[0020] As an improvement of the above-mentioned scheme, the oblique shear test fixture includes an upper fixture for applying pressure to the stress absorption layer specimen, a lower fixture for supporting the stress absorption layer specimen, a first adjusting member for adjusting the pressure angle of the upper fixture and a second adjusting member for adjusting the supporting angle of the lower fixture; the upper fixture includes a pressure plate, a top surface pressure portion for applying pressure to the top surface of the stress absorption layer specimen and an upper side pressure portion for applying pressure to the side surface of the stress absorption layer specimen, the pressure plate is respectively connected to the top surface pressure portion and the upper side pressure portion, and is used to transfer the pressure of the external pressure mechanism to the top surface pressure portion and the upper side pressure portion; the lower fixture includes a support member, a bottom surface support portion for positioning the bottom surface of the stress absorption layer specimen and a lower side support portion for positioning the other side surface of the stress absorption layer specimen, the support member is respectively connected to the bottom surface support portion and the lower side support portion, and is used to support the bottom surface support portion and the lower side support portion.

[0021] Correspondingly, the present invention also provides a computer device, including a memory and a processor, wherein the memory stores a computer program, wherein the processor implements the steps of the above-mentioned method for evaluating the anti-cracking performance of an asphalt stress absorption layer when executing the computer program.

[0022] The implementation of the present invention has the following beneficial effects:

[0023] The method for evaluating the anti-cracking performance of the asphalt stress absorption layer of the present invention constructs the interlayer bonding coefficient and the interlayer stress absorption coefficient by monitoring the index information during the oblique shear test, so as to characterize the ability of the stress absorption layer to absorb stress when the road surface is subjected to load and the ability of the stress absorption layer to absorb stress and convert it into displacement for consumption;

[0024] At the same time, the present invention constructs a special evaluation system based on the interlayer bonding coefficient and the interlayer stress absorption coefficient, which can realize an intuitive and efficient evaluation of the anti-cracking performance; it is no longer necessary to perform direct shear tests, low-temperature semicircular bending tests and interlayer pull-out tests on the asphalt stress absorption layer, and the operation is convenient and the accuracy is high. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a flow chart of a first embodiment of a method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to the present invention;

[0026] Figure 2 It is a front view of the oblique shear test fixture of the present invention;

[0027] Figure 3 is a stereoscopic diagram of the oblique shear test fixture of the present invention;

[0028] Figure 4 It is a schematic diagram of the force during the oblique shear test of the stress absorbing layer specimen in the present invention;

[0029] Figure 5 is a flow chart of a second embodiment of the method for evaluating the anti-cracking performance of an asphalt stress absorbing layer of the present invention;

[0030] Figure 6 It is a schematic diagram of the relationship between the load, vertical displacement and lateral displacement when the test temperature is 15°C in the present invention;

[0031] Figure 7 It is a schematic diagram of the changing relationship between the stress load, vertical displacement and lateral displacement when the test temperature is 25°C in the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. It is hereby stated that the directional terms such as up, down, left, right, front, back, inside, outside, etc. that appear or will appear in the text of the present invention are only based on the accompanying drawings of the present invention, and are not specific limitations of the present invention.

[0033] See also Figure 1 , Figure 1 The flowchart of the first embodiment of the method for evaluating the anti-cracking performance of an asphalt stress absorbing layer of the present invention is shown, which includes:

[0034] S101, performing an oblique shear test on the stress absorption layer specimen, and collecting index information during the oblique shear test;

[0035] The index information includes shear angle, load, vertical displacement, lateral displacement, interlayer displacement and adhesion of stress absorbing layer;

[0036] Accordingly, the steps of performing an oblique shear test on the stress absorbing layer specimen and collecting index information during the oblique shear test include:

[0037] (1) Placing the stress absorbing layer specimen in a temperature-controlled box for insulation treatment;

[0038] The stress absorbing layer specimen is placed in a temperature-controlled box with a preset temperature for insulation for more than 5 hours. The test temperatures are 15°C and 25°C respectively, but this is not a limitation and can be adjusted according to actual conditions.

[0039] (2) Use an oblique shear test fixture to perform an oblique shear test on the stress absorbing layer specimen;

[0040] like Figure 2 and Figure 3 As shown, the oblique shear test fixture includes an upper fixture 1 for applying pressure to the stress absorption layer specimen 100, a lower fixture 2 for supporting the stress absorption layer specimen 100, a first adjustment member 3 for adjusting the pressure angle of the upper fixture 1, and a second adjustment member 4 for adjusting the support angle of the lower fixture 2. Among them, the upper clamp 1 includes a pressure plate 11, a top surface pressure portion 12 for applying pressure to the top surface of the stress absorption layer specimen 100, and an upper side pressure portion 13 for applying pressure to the side of the stress absorption layer specimen 100. The pressure plate 11 is connected to the top surface pressure portion 12 and the upper side pressure portion 13 respectively, and the pressure plate 11 is used to transfer the pressure of the external pressure mechanism to the top surface pressure portion 12 and the upper side pressure portion 13; the lower clamp 2 includes a support member 21, a bottom surface support portion 22 for positioning the bottom surface of the stress absorption layer specimen 100, and a lower side support portion 23 for positioning the other side of the stress absorption layer specimen 100. The support member 21 is connected to the bottom surface support portion 22 and the lower side support portion 23 respectively, and is used to support the bottom surface support portion 22 and the lower side support portion 23.

[0041] Accordingly, since the stress absorption layer specimen 100 is generally a cylindrical structure, in this embodiment, the top pressure portion 12 and the bottom support portion 22 are both designed as planar structures that match the top surface and the ground of the stress absorption layer specimen 100; and the upper pressure portion 13 and the lower support portion 23 are both designed as arc surface structures that match the side surfaces of the stress absorption layer specimen 100.

[0042] When conducting the oblique shear test, the oblique shear test fixture can be set below the lower pressure head, and a roller can be set between the contact surface of the oblique shear test fixture and the lower pressure head. The oblique shear test fixture and the stress absorption layer specimen 100 are installed on the UTM testing machine, and the shear angle is 45°, so that the stress absorption layer is between the upper fixture 1 and the lower fixture 2. During the pressurization process, the pressure of the lower pressure head is directly transmitted to the first adjustment member 3, and then to the pressure plate 11, the top surface pressure part 12 and the upper side pressure part 13, and cooperate with the lower fixture 2, so as to convert the pressure into a force along the predetermined shear angle.

[0043] In this embodiment, the longitudinal sections of the first adjusting member 3 and the second adjusting member 3 are triangular structures, and the top surface of the first adjusting member 3 is parallel to the bottom surface of the second adjusting member 4. When the test needs to adjust different shear angles, the first adjusting member 3 and the second adjusting member 3 with different angles can be replaced to adjust the shear angle, and ensure that the pressure is applied vertically to the first adjusting member 3.

[0044] In addition, in order to adapt to stress absorbing layer specimens 100 of different heights, an auxiliary chassis 5 can be added, and the auxiliary chassis 5 can be arranged between the stress absorbing layer specimen 100 and the bottom support portion 22 to cooperate with the oblique shear test. At the same time, in order to adapt to stress absorbing layer specimens 100 of different diameters, an auxiliary adapter 6 can be added, and the auxiliary adapter 6 can be arranged between the stress absorbing layer specimen 100 and the upper side pressure portion 13 / lower side support portion 23 to cooperate with the oblique shear test.

[0045] Furthermore, a sliding base 7 may be additionally provided, and the sliding base 7 may ensure that the stress absorption layer specimen 100 is continuously stressed along a shearing surface of a predetermined shearing angle during the test.

[0046] (3) During the oblique shear test, the stress absorbing layer specimen is loaded at a uniform speed until the stress absorbing layer specimen reaches the target degree of damage;

[0047] (4) Collect the shear angle, load, vertical displacement, lateral displacement and adhesion of the stress absorbing layer during the test;

[0048] At the beginning of pressurization, the loading rate is 10 mm / min, and the loading is uniformly carried out until the stress absorption layer specimen is severely damaged. At this time, the shear angle, load, vertical displacement, lateral displacement and adhesion of the stress absorption layer during the test are recorded to obtain the changing relationship between vertical displacement-load and vertical displacement-lateral displacement during the test.

[0049] (5) After the oblique shear test, remove the stress absorption layer specimen for static treatment;

[0050] (6) Measure the interlayer displacement between the upper and lower test blocks of the stress absorption layer specimen.

[0051] After the oblique shear test, the stress absorption layer specimen was removed and left to stand for 1 hour, and then the interlayer displacement between the upper test block and the lower test block was measured using a vernier caliper.

[0052] S102, calculating the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information;

[0053] like Figure 4 As shown in the figure, the energy conservation law of the stress absorption layer specimen during the oblique shear test satisfies the following formula:

[0054]

[0055] Accordingly, according to the index information, the steps of calculating the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer specimen include:

[0056] (1) Calculate the interlayer direction load based on the shear angle and the load;

[0057] According to the following formula, the interlayer direction load F is calculated ’ :

[0058] F'=F×sinα

[0059] Among them, α is the shear angle, F is the force load;

[0060] (2) Calculate the decomposition of vertical displacement in the interlayer direction based on vertical displacement and shear angle;

[0061] According to the following formula, the decomposed displacement s1 of the vertical displacement in the interlayer direction is calculated:

[0062] s1=L1×sinα

[0063] Among them, α is the shear angle, L1 is the vertical displacement;

[0064] (3) Calculate the decomposition displacement of the lateral displacement in the interlayer direction based on the lateral displacement and shear angle;

[0065] According to the following formula, the decomposed displacement s2 of the lateral displacement in the interlayer direction is calculated:

[0066] s2=L2×cosα

[0067] Among them, α is the shear angle, L2 is the lateral displacement;

[0068] (4) Calculate the stress absorption displacement based on the decomposition of the vertical displacement in the interlayer direction, the decomposition of the lateral displacement in the interlayer direction, and the interlayer dislocation displacement;

[0069] The stress absorption displacement Δx is calculated according to the following formula:

[0070] Δx=s1+s2-x

[0071] Among them, s1 is the decomposition displacement of vertical displacement in the interlayer direction, s2 is the decomposition displacement of lateral displacement in the interlayer direction, and x is the interlayer dislocation displacement;

[0072] (5) Calculate the interlayer bonding coefficient of the stress absorbing layer specimen according to the stress absorbing layer bonding force, stress absorbing displacement, interlayer direction load and vertical displacement decomposed in the interlayer direction;

[0073] According to the following formula, the interlayer bonding coefficient K1 of the stress absorption layer specimen is calculated:

[0074]

[0075] in,

[0076] K1 is the interlayer bonding coefficient, and its physical meaning is the ability of the stress absorbing layer to absorb stress when the pavement is subjected to load;

[0077] Δx is the stress absorption displacement, F t is the bonding force of the stress absorbing layer, s1 is the decomposed displacement of the vertical displacement in the interlayer direction, F ’ is the inter-layer direction load;

[0078] (6) The interlaminar stress absorption coefficient of the stress absorption layer specimen is calculated based on the stress absorption displacement, the decomposition displacement of the vertical displacement in the interlaminar direction, and the decomposition displacement of the lateral displacement in the interlaminar direction.

[0079] According to the following formula, the interlaminar stress absorption coefficient K2 of the stress absorption layer specimen is calculated:

[0080] K2=∫0 t Δxdt / ∫0 t (s1+s2)dt

[0081] Among them, K2 is the interlayer stress absorption coefficient, and its physical meaning is the ability of the stress absorption layer to absorb stress and convert it into displacement for consumption when the road surface is subjected to load;

[0082] Δx is the stress absorption displacement, s1 is the decomposition displacement of the vertical displacement in the interlayer direction, and s2 is the decomposition displacement of the lateral displacement in the interlayer direction.

[0083] Therefore, the anti-cracking performance evaluation method for asphalt stress absorption layer of the present invention constructs interlayer bonding coefficient and interlayer stress absorption coefficient by monitoring index information during the oblique shear test, so as to characterize the ability of the stress absorption layer to absorb stress when the pavement is subjected to load and the ability of the stress absorption layer to absorb stress and convert it into displacement for consumption;

[0084] S103, evaluating the anti-cracking performance of the stress absorption layer specimen according to the interlayer bonding coefficient and the interlayer stress absorption coefficient.

[0085] The interlayer bonding coefficient and interlayer stress absorption coefficient are positively correlated with the crack resistance.

[0086] Specifically, the steps of evaluating the anti-cracking performance of the stress absorption layer specimen according to the interlayer bonding coefficient and the interlayer stress absorption coefficient include:

[0087] (1) When the interlayer stress absorption coefficient is greater than the first absorption threshold and the interlayer bonding coefficient is greater than or equal to the second bonding threshold, or the interlayer stress absorption coefficient is greater than or equal to the second absorption threshold and the interlayer bonding coefficient is greater than the first bonding threshold, the crack resistance of the stress absorption layer specimen is "good"; wherein the first absorption threshold is greater than the second absorption threshold, and the first bonding threshold is greater than the second bonding threshold;

[0088] (2) When the interlayer stress absorption coefficient is less than the second absorption threshold and the interlayer bonding coefficient is less than or equal to the first bonding threshold, or the interlayer stress absorption coefficient is less than or equal to the first absorption threshold and the interlayer bonding coefficient is less than the second bonding threshold, the crack resistance of the stress absorption layer specimen is “average”;

[0089] (3) Otherwise, the crack resistance of the stress absorption layer specimen is "good"

[0090] In this embodiment, the first absorption threshold value may be set to 0.6, the second absorption threshold value may be set to 0.3, the first adhesion threshold value may be set to 1, and the second adhesion threshold value may be set to 0.5. Therefore:

[0091] (1) When K2>0.6 and K1≥0.5, or K2≥0.3 and K1>1, the anti-cracking performance of the asphalt stress absorbing layer is "good";

[0092] (2) When K2<0.3 and K1≤1, or K2≤0.6 and K1<0.5, the anti-cracking performance of the asphalt stress absorbing layer is “average”;

[0093] (3) When K2<0.3 and K1>1, or 0.3≤K2≤0.6 and 0.5≤K1≤1, or K2>0.6 and K1<0.5, the anti-cracking performance of the asphalt stress absorption layer is "good".

[0094] The corresponding evaluation indicators are shown in Table 1 below:

[0095] Evaluation indicators <![CDATA[K1<0.5]]> <![CDATA[0.5≤K1≤1]]> <![CDATA[K1>1]]> <![CDATA[K2<0.3]]> generally generally better <![CDATA[0.3≤K2≤0.6]]> generally better good <![CDATA[K2>0.6]]> better good good

[0096] It should be noted that when the crack resistance of the stress absorption layer specimens is at the same level, the crack resistance performance is ranked based on "interlayer stress absorption coefficient K2 as the main factor and interlayer bonding coefficient K1 as the auxiliary factor".

[0097] Therefore, the present invention constructs a special evaluation system based on the interlayer bonding coefficient and the interlayer stress absorption coefficient, which can realize an intuitive and efficient evaluation of the anti-cracking performance; it is no longer necessary to perform direct shear tests, low-temperature semicircular bending tests and interlayer pull-out tests on the asphalt stress absorption layer, and the operation is convenient and the accuracy is high.

[0098] See also Figure 5 , Figure 5A flow chart of a second embodiment of the method for evaluating the anti-cracking performance of an asphalt stress absorbing layer of the present invention is shown, which includes:

[0099] S201, constructing a stress absorption layer specimen;

[0100] Accordingly, the steps of forming the stress absorbing layer specimen include:

[0101] (1) Construct asphalt mixture plate specimens;

[0102] In accordance with the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" T0703-2011, a wheel roller is used to form asphalt mixture plate specimens with a size of 300mm×300mm×55mm.

[0103] Accordingly, the gradation of the asphalt mixture plate specimens is shown in Table 2 below:

[0104] Table 2

[0105]

[0106] At the same time, the asphalt-stone ratio and volume index of the asphalt mixture plate specimen are shown in Table 3 below:

[0107] Table 3

[0108]

[0109] (2) Spreading a stress absorbing layer on the asphalt mixture plate specimen;

[0110] It should be noted that the stress absorption layer types are divided into three types: rubber asphalt stress absorption layer, single-layer rubber asphalt macadam stress absorption layer and double-layer rubber asphalt macadam stress absorption layer. The following are detailed descriptions of the three types of stress absorption layers:

[0111] 1. Rubber asphalt stress absorption layer

[0112] When the stress absorbing layer is a rubber asphalt stress absorbing layer, when spreading the stress absorbing layer on the asphalt mixture plate specimen: directly spread the rubber asphalt on the asphalt mixture plate specimen.

[0113] For example, to construct asphalt mixture plate specimen 1: After the asphalt mixture plate specimen is formed, immediately spread 2.0kg / m 3 of rubber asphalt on plate specimens.

[0114] 2. Single-layer rubber asphalt crushed stone stress absorption layer

[0115] When the stress absorbing layer is a single-layer rubber asphalt crushed stone stress absorbing layer, when spreading the stress absorbing layer on the asphalt mixture plate specimen: first spread the rubber asphalt on the asphalt mixture plate specimen, then spread the crushed stone pre-wrapped with rubber asphalt on the rubber asphalt, and lightly press the crushed stone to embed the crushed stone into the asphalt;

[0116] For example, to construct asphalt mixture plate specimen 2: After the asphalt mixture plate specimen is formed, immediately spread 2.0kg / m 3 180℃ hot rubber asphalt is applied on the plate specimen, and then 10-15mm single-particle crushed stone pre-wrapped with rubber asphalt is evenly spread on the rubber asphalt according to 80% of the spreading area, and the crushed stone is lightly pressed with an iron block to embed the crushed stone into the asphalt.

[0117] 3. Double-layer rubber asphalt crushed stone stress absorption layer

[0118] When the stress absorbing layer is a double-layer rubber asphalt crushed stone stress absorbing layer, when spreading the stress absorbing layer on the asphalt mixture plate specimen: spread the rubber asphalt on the asphalt mixture plate specimen, spread the crushed stone pre-wrapped with rubber asphalt on the rubber asphalt, lightly press the crushed stone to embed the crushed stone into the asphalt, and then spread the rubber asphalt, spread the crushed stone pre-wrapped with rubber asphalt on the rubber asphalt, and lightly press the crushed stone to embed the crushed stone into the asphalt.

[0119] For example, to construct asphalt mixture plate specimen 3: After the asphalt mixture plate specimen is formed, immediately spread 2.0kg / m 3 180℃ hot rubber asphalt is applied to the plate-shaped specimen, and then 10-15mm single-particle crushed stone pre-wrapped with rubber asphalt is evenly spread on the rubber asphalt according to 80% of the spreading area. The crushed stone is lightly pressed with an iron block to embed the crushed stone into the asphalt; then 2.0kg / m 3 180℃ hot rubber asphalt, evenly spread 5-10mm single-particle crushed stone pre-wrapped with rubber asphalt on the rubber asphalt according to 80% of the spreading area, and lightly press the crushed stone with an iron block to embed the crushed stone into the asphalt.

[0120] (3) The asphalt mixture plate specimens after the stress absorption layer is spread are subjected to static and heat preservation treatments in sequence;

[0121] The asphalt mixture plate specimens together with the test mold were placed at room temperature for 48 hours and then placed in a 60°C oven for 5 hours.

[0122] (4) evenly paving the asphalt mixture on the stress absorption layer of the asphalt mixture plate specimen after the insulation treatment, and rolling it into shape;

[0123] The mixed asphalt mixture is immediately and evenly spread on top of the stress absorbing layer and compacted into shape using a wheel compactor.

[0124] (5) placing the compacted asphalt mixture plate specimens in a static state and demoulding the specimens in turn;

[0125] The asphalt mixture plate specimens together with the test molds were placed at room temperature and demolded after 48 hours.

[0126] (6) performing coring on the demoulding asphalt mixture plate specimen to form a stress absorption layer specimen;

[0127] Use a core drill to obtain cylindrical stress absorption layer specimens.

[0128] (7) The end surface of the stress absorbing layer specimen is ground flat so that the stress absorbing layer is located in the middle of the stress absorbing layer specimen.

[0129] The end surface of the stress absorption layer specimen was ground flat, and the size of the stress absorption layer specimen was controlled to And ensure that the stress absorbing layer is in the middle position of the stress absorbing layer specimen.

[0130] S202, performing an oblique shear test on the stress absorbing layer specimen, and collecting index information during the oblique shear test;

[0131] For example, after asphalt mixture plate specimen 1 (rubber asphalt stress absorption layer), asphalt mixture plate specimen 2 (single-layer rubber asphalt crushed stone stress absorption layer) and asphalt mixture plate specimen 3 (double-layer rubber asphalt crushed stone stress absorption layer) are constructed respectively according to step S201, the oblique shear test is performed on the stress absorption layer specimen according to step S201, and the index information at temperatures of 15°C and 25°C can be obtained, and the change relationship between the load, vertical displacement and lateral displacement during the test process can be obtained (see Figure 6 and Figure 7 , where line a represents the variation relationship of specimen 1, line b represents the variation relationship of specimen 2, and line c represents the variation relationship of specimen 3);

[0132] Accordingly, the index information of the specimen when loading stops is shown in Table 4 below:

[0133] Table 4

[0134]

[0135] S203, calculating the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information;

[0136] Correspondingly, according to step S203, the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen at 15°C can be calculated:

[0137] For specimen 1: K1 = 0.59, K2 = 0.16; it can be obtained that the crack resistance is "average";

[0138] For specimen 2: K1 = 0.60, K2 = 0.42; it can be obtained that the crack resistance is "good";

[0139] For specimen 3: K1 = 0.77, K2 = 0.63; it can be obtained that the crack resistance is "good";

[0140] Similarly, according to step S203, the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen at 25°C can be calculated:

[0141] For specimen 1: K1 = 0.50, K2 = 0.38; it can be obtained that the crack resistance is "good";

[0142] For specimen 2: K1 = 0.65, K2 = 0.48; it can be obtained that the crack resistance is "good";

[0143] For specimen 3: K1 = 1.49, K2 = 0.68. It can be seen that the crack resistance is "good";

[0144] Among them, the crack resistance of specimens 1 and 2 is at the same level. At this time, K2 of specimen 1 is 0.38, and K2 of specimen 2 is 0.48, so specimen 2 is better than specimen 1.

[0145] S204, evaluating the anti-cracking performance of the stress absorption layer specimen according to the interlayer bonding coefficient and the interlayer stress absorption coefficient.

[0146] It can be seen from the above that under the same temperature conditions, in this embodiment, the interlayer bonding coefficient is ranked as follows: specimen 3> specimen 2> specimen 1, and the interlayer stress absorption coefficient is ranked as follows: specimen 3> specimen 2> specimen 1. Therefore, the double-layer rubber asphalt macadam stress absorption layer has the best anti-cracking performance, the single-layer rubber asphalt macadam stress absorption layer has the second best, and the rubber asphalt stress absorption layer has the lowest.

[0147] It should be noted that the double-layer rubber asphalt crushed stone stress absorption layer is sprinkled with asphalt containing graded crushed stone, which has greater elasticity and therefore better crack resistance; the rubber asphalt stress absorption layer is just the opposite, it is not sprinkled with crushed stone and has worse elasticity, so when subjected to shear load, its elastic stress absorption capacity is worse.

[0148] Therefore, the evaluation results of the above anti-cracking performance are consistent with the theoretical results, and the evaluation method of the anti-cracking performance of the asphalt stress absorption layer of the present invention is intuitive, accurate and effective.

[0149] Correspondingly, the present invention discloses a computer device, including a memory and a processor, wherein the memory stores a computer program, wherein the processor implements the steps of the above-mentioned method for evaluating the anti-cracking performance of an asphalt stress absorption layer when executing the computer program.

[0150] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.

Claims

1. A method for evaluating the anti-cracking performance of an asphalt stress absorbing layer, characterized in that: include: Performing an oblique shear test on the stress absorbing layer specimen, and collecting index information during the oblique shear test, wherein the index information includes shear angle, force load, vertical displacement, lateral displacement, interlayer displacement and adhesion of the stress absorbing layer; Calculating the interlayer bonding coefficient and interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information; The anti-cracking performance of the stress absorption layer specimen is evaluated according to the interlayer bonding coefficient and the interlayer stress absorption coefficient.

2. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1, characterized in that: The step of calculating the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information comprises: Calculate the interlayer direction load according to the shear angle and the force load; Calculate the decomposed displacement of the vertical displacement in the interlayer direction according to the vertical displacement and the shear angle; Calculate the decomposition displacement of the lateral displacement in the interlayer direction according to the lateral displacement and the shear angle; Calculate the stress absorption displacement according to the decomposed displacement of the vertical displacement in the interlayer direction, the decomposed displacement of the lateral displacement in the interlayer direction and the interlayer dislocation displacement; Calculate the interlayer bonding coefficient of the stress absorbing layer specimen according to the stress absorbing layer bonding force, stress absorbing displacement, interlayer direction load and vertical displacement decomposed in the interlayer direction; The interlaminar stress absorption coefficient of the stress absorption layer specimen is calculated according to the stress absorption displacement, the decomposed displacement of the vertical displacement in the interlaminar direction, and the decomposed displacement of the lateral displacement in the interlaminar direction.

3. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1 or 2, characterized in that: The step of calculating the interlayer bonding coefficient and the interlayer stress absorption coefficient of the stress absorption layer specimen according to the index information comprises: According to formula F ’ =F×sinα, calculate the interlayer direction load F ’ , where α is the shear angle and F is the load; According to the formula s1 = L1 × sinα, the vertical displacement is calculated as the decomposed displacement s1 in the interlayer direction, where L1 is the vertical displacement; According to the formula s2 = L2 × cosα, the lateral displacement is calculated to decompose the displacement s2 in the interlayer direction, where L2 is the lateral displacement; According to the formula Δx=s1+s2-x, the stress absorption displacement Δx is calculated, where x is the interlayer displacement; According to the formula Calculate the interlayer bonding coefficient K1 of the stress absorption layer specimen, where F t is the bonding force of the stress absorbing layer; According to the formula The interlaminar stress absorption coefficient K2 of the stress absorption layer specimen is calculated.

4. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1, characterized in that: The interlayer bonding coefficient and interlayer stress absorption coefficient are positively correlated with the anti-cracking performance.

5. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1 or 4, characterized in that: The step of evaluating the anti-cracking performance of the stress absorption layer specimen according to the interlayer bonding coefficient and the interlayer stress absorption coefficient comprises: When the interlayer stress absorption coefficient is greater than the first absorption threshold and the interlayer bonding coefficient is greater than or equal to the second bonding threshold, or the interlayer stress absorption coefficient is greater than or equal to the second absorption threshold and the interlayer bonding coefficient is greater than the first bonding threshold, the crack resistance of the stress absorption layer specimen is "good", the first absorption threshold is greater than the second absorption threshold, and the first bonding threshold is greater than the second bonding threshold; When the interlayer stress absorption coefficient is less than the second absorption threshold and the interlayer bonding coefficient is less than or equal to the first bonding threshold, or the interlayer stress absorption coefficient is less than or equal to the first absorption threshold and the interlayer bonding coefficient is less than the second bonding threshold, the crack resistance of the stress absorption layer specimen is "normal"; Otherwise, the crack resistance of the stress absorption layer specimen is "good".

6. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1, characterized in that: The molding step of the stress absorbing layer specimen comprises: Construct asphalt mixture plate specimens; Spreading a stress absorbing layer on the asphalt mixture plate-shaped specimen; The asphalt mixture plate-shaped specimen after the stress absorption layer is spread is subjected to static and heat preservation treatment in sequence; Evenly paving the asphalt mixture on the stress absorption layer of the asphalt mixture plate specimen after the thermal insulation treatment, and rolling it into shape; The asphalt mixture plate-shaped specimen after rolling is sequentially subjected to static standing and demoulding treatments; performing coring on the demoulding asphalt mixture plate-shaped specimen to form a stress absorption layer specimen; The end surface of the stress absorption layer specimen is polished to make the stress absorption layer located in the middle of the stress absorption layer specimen.

7. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 6, characterized in that: The step of spreading the stress absorbing layer on the asphalt mixture plate-shaped specimen comprises: When the stress absorbing layer is a rubber asphalt stress absorbing layer, spreading the rubber asphalt on the asphalt mixture plate-shaped specimen; When the stress absorbing layer is a single-layer rubber asphalt crushed stone stress absorbing layer, the rubber asphalt is spread on the asphalt mixture plate-shaped test piece, the crushed stone pre-wrapped with rubber asphalt is spread on the rubber asphalt, and the crushed stone is lightly pressed to embed the crushed stone into the asphalt; When the stress absorbing layer is a double-layer rubber asphalt crushed stone stress absorbing layer, spread rubber asphalt on the asphalt mixture plate specimen, spread crushed stone pre-coated with rubber asphalt on the rubber asphalt, lightly press the crushed stone to embed the crushed stone into the asphalt, spread rubber asphalt again, spread crushed stone pre-coated with rubber asphalt on the rubber asphalt, and lightly press the crushed stone to embed the crushed stone into the asphalt.

8. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 1, characterized in that: The step of performing an oblique shear test on the stress absorbing layer specimen and collecting index information during the oblique shear test comprises: Placing the stress absorbing layer specimen in a temperature-controlled box for heat preservation treatment; An oblique shear test fixture is used to perform an oblique shear test on the stress absorbing layer specimen; During the oblique shear test, the stress absorbing layer specimen is loaded at a uniform speed until the stress absorbing layer specimen reaches a target degree of damage; Collect the shear angle, load, vertical displacement, lateral displacement and adhesion of the stress absorbing layer during the test; After the oblique shear test is completed, the stress absorption layer specimen is removed for static treatment; The interlayer displacement between the upper test block and the lower test block of the stress absorbing layer test piece is measured.

9. The method for evaluating the anti-cracking performance of an asphalt stress absorbing layer according to claim 8, characterized in that: The oblique shear test fixture comprises an upper fixture for applying pressure to the stress absorbing layer specimen, a lower fixture for supporting the stress absorbing layer specimen, a first adjusting member for adjusting the pressure angle of the upper fixture, and a second adjusting member for adjusting the supporting angle of the lower fixture; The upper fixture comprises a pressure plate, a top surface pressure portion for applying pressure to the top surface of the stress absorbing layer specimen, and an upper side pressure portion for applying pressure to the side surface of the stress absorbing layer specimen, the pressure plate is connected to the top surface pressure portion and the upper side pressure portion, respectively, and is used to transmit the pressure of the external pressure mechanism to the top surface pressure portion and the upper side pressure portion; The lower clamp includes a support member, a bottom support portion for positioning the bottom surface of the stress absorption layer specimen, and a lower side support portion for positioning the other side surface of the stress absorption layer specimen. The support member is respectively connected to the bottom support portion and the lower side support portion, and is used to support the bottom support portion and the lower side support portion.

10. A computer device comprising a memory and a processor, wherein the memory stores a computer program, characterized in that: When the processor executes the computer program, the steps of the method according to any one of claims 1 to 9 are implemented.

Citation Information

Patent Citations

  • Multi-angle large-deformation shear test fixture of structure stress absorption layer of pavement

    CN103674696A

  • Device and method for evaluating influence of soaking environment on interlayer shear resistance of asphalt pavement

    CN117250106A

  • Method for evaluating interlayer bonding strength of asphalt pavement

    CN118111909A

  • Angle interlamination bonding capability test devices of shearing more

    CN206671165U